A CYCLIC-TIME MODEL FOR ECLIPSE PREDICTION IN MESOAMERICA AND THE STRUCTURE OF THE ECLIPSE TABLE IN THE DRESDEN CODEX. Issue 2 (8th December 2017) - Justeson, John
Abstract: This study describes, illustrates, and applies an "eclipse family" representation for the cyclic timing of eclipses in Mesoamerica. This theoretical construct is based on daykeepers' approach to divination, anchored in the divinatory calendar (DC); empirically, it emerges from data on the timing of eclipses in Lowland Mayan 1 territory between 100b.c.e. and 1500c.e. drawn from Espenak and Meuss's (2007, 2009) eclipse canons. An eclipse family consists of a sequence of stations on which an eclipse might be visible in Mesoamerica – one every 88 new or full moons for 170 to 200 years, restricted to one of three DC zones. Cyclic and linear time relationships among dates of eclipses follow from this representation: intervals between successive stations in concurrent families in the same zone, and between successive stations across zones; between successive families in a zone; and among the first or last stations of families, within and across zones. One and only one eclipse-family representation fits the lunar stations of the Dresden Codex; its properties show that it is a solar eclipse table. In real time, the table pertains to a 405-month interval sometime between 1076 and 1148c.e., most likely from April 19, 1083c.e. to January 16, 1116c.e.